2012
DOI: 10.1002/cncr.27603
|View full text |Cite
|
Sign up to set email alerts
|

Association of EGFR mutation or ALK rearrangement with expression of DNA repair and synthesis genes in never‐smoker women with pulmonary adenocarcinoma

Abstract: BACKGROUND: Epidermal growth factor receptor (EGFR) mutation and anaplastic lymphoma kinase (ALK) rearrangement may predict the outcome of targeted drug therapy and also are associated with the efficacy of chemotherapy in patients with nonsmall cell lung cancer (NSCLC). The authors of this report investigated the relation of EGFR mutation or ALK rearrangement status and the expression of DNA repair or synthesis genes, including excision repair cross-complementing 1 (ERCC1), ribonucleotide reductase subunit M1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 38 publications
2
25
1
Order By: Relevance
“…In addition, only 10% of patients did not harbor any detected mutation in these genes. Ren et al reported EGFR mutation in 70% and ALK rearrangement in 9.6% in adenocarcinomas from never-smoker Chinese women (see Supplemental Table 5 for summary of these studies) [27]. The incidences of mutation detected in this study are consistent with those of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, only 10% of patients did not harbor any detected mutation in these genes. Ren et al reported EGFR mutation in 70% and ALK rearrangement in 9.6% in adenocarcinomas from never-smoker Chinese women (see Supplemental Table 5 for summary of these studies) [27]. The incidences of mutation detected in this study are consistent with those of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Thus the obtained biomarker results are in concordance with previous reports and demonstrate that the used method is feasible for multiple biomarker testing in a routine setting. In line with our previous and Gandara’s report [20][21], the ERCC1 levels in the patients with EGFR mutation were significantly lower than the wild type, which indicated that EGFR mutation could also be helpful as a selection criterion for the optimal chemotherapy regimen.…”
Section: Discussionsupporting
confidence: 89%
“…Gandara et al investigated the association between ERFR mutation and ERCC1 mRNA levels in 1207 NSCLC tumor samples, and reported that tumors harboring activating EGFR mutations were more likely to express low levels of ERCC1 mRNA [17]. Re et al also reported that specimens harboring EGFR mutations were likely to have low expression of ERCC1 [21], and Lee et al, using immunohistochemistry, found a significant correlation between EGFR mutation and low levels of ERCC1 in tumor cells [22]. In agreement with these results, we found a significant correlation between ERCC1 expression and EGFR mutation (P = 0.030).…”
Section: Discussionmentioning
confidence: 99%
“…This method is able to detect 11 different mutations in the presence of a 100- to 1,000-fold wild-type EGFR background [16]. These 11 mutations account for 95% of all EGFR mutations found in Japanese patients, suggesting that the remaining 5% cannot be detected by the PNA-LNA PCR clamp method [21]. Therefore it is possible some patients in whom mutations were not detected may actually have harbored mutations.…”
Section: Discussionmentioning
confidence: 99%